If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + -4 = 2w + -11 Reorder the terms: -4 + 4w = 2w + -11 Reorder the terms: -4 + 4w = -11 + 2w Solving -4 + 4w = -11 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -4 + 4w + -2w = -11 + 2w + -2w Combine like terms: 4w + -2w = 2w -4 + 2w = -11 + 2w + -2w Combine like terms: 2w + -2w = 0 -4 + 2w = -11 + 0 -4 + 2w = -11 Add '4' to each side of the equation. -4 + 4 + 2w = -11 + 4 Combine like terms: -4 + 4 = 0 0 + 2w = -11 + 4 2w = -11 + 4 Combine like terms: -11 + 4 = -7 2w = -7 Divide each side by '2'. w = -3.5 Simplifying w = -3.5
| 6.6+6n=7n-0.4 | | 2x+1=x+37 | | -104=8i | | 30x+(20-x)x=100 | | h-9=-13 | | f(x)=-1.5x+10 | | 4.5(7)+4.5(6)= | | -20=-4e-6e | | 270+230+240+250= | | 101.75*3.65= | | -8t=32 | | J-15=-27 | | 2x+5=10.50 | | 5x-15=-7+7x | | 8z-17=-59+z | | 125t=0 | | N-.5=10 | | 19x^2+38x+1=0 | | -3(t-2)+5t=7t-7 | | 1-3x=12x-6 | | -14x-9=201 | | 6cosx+6secx=13 | | -11x+14=129 | | -3x-20=155 | | =5x-1 | | 11x+9=3x-2 | | 6(3n-4)=(7n+9)+2 | | (9x-9)=(4x+16) | | 3x-3x+12=12 | | 13+3=81 | | x+3.5=25 | | (x+3).5=25 |